Retelling History Through Imagined Spaces: Examples of Literary Cartography from Select Postcolonial Malayalam Novels - Sethuparvathy S.; Smita Jha (HyperCultura)
Abstract: Cartography, or the art of mapmaking, has been used by past and present writers to locate the settings of their stories. When it comes to imaginary settings, at times, the act of marking the place on the map of the real world implies that it has a different intention than just being the backdrop of the action of the story. Using select indigenous Indian novels translated from the Malayalam language to English, this paper will study how fictional spaces created and marked on the map by writers of Indian regional languages become a counter-narrative for recorded history. The paper will examine how, in a postcolonial context, a narrative text becomes an ethnographic and social commentary that has tried to transcend local boundaries and identify itself as a resistance narrative to the hegemonic powers. Questions like what happens when history, narrative, and geography merge; how the history of a place or space influences one’s identity, knowledge, and power, especially in an imagined topography; how these imagined spaces remain contested and unstable; how Malayali writers become cartographers, locating an imagined space within real ones, how they offer a silent critique of known Indian colonial history, etc., will be addressed.